KESALAHAN EJAAN DALAM SURAT PERMINTAAN KETERANGAN AHLI BAHASA DARI POLDA MALUKU UTARA - Fida Febriningsih (Gramatika: Jurnal Ilmiah Kebahasaan dan Kesastraan, 2019)
The purpose of this study is to find out what spelling errors are contained in the Letter of Request for Expert Opinion of Language Experts from the North Maluku Regional Police and provide recommendations for improvements as additional information for writing the next letter. This study uses a description method with three stages, namely the stage of providing data, the data analysis phase, and the stage of presenting the results of data analysis. The results of the study found letters usage errors, word writing errors, punctuation usage errors, and absorption elements writing errors.